The Choice of the Approach to Off-Pump Surgical Treatment for Combined Occlusive and Stenotic Lesions of Brachiocephalic and Coronary Arteries - Usenko, O. Y.; Beleiovych, V. V.; Gabriyelian, A. V. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Summary. The heart and brain are the most dependent organs on the violation of blood flow. In fact, combined atherosclerotic lesions of the carotid and coronary arteries are found in 5.9 to 22% of cardiac patients. Objective. To improve the results of treatment for combined occlusive and stenotic lesions brachiocephalic and coronary arteries by designing the surgical approach for the patients with multifocal atherosclerosis. Materials and methods. The results of surgical treatment of 62 patients with combined atherosclerotic occlusion-stenotic lesions of the carotid and coronary arteries were analyzed. Depending on the surgical approach used, patients were divided into two groups: one-step (35) on two vascular pools and stage operations (27). The survey protocol included general clinical and specific methods of heart and brain testing. Results and discussion. Satisfactory results of surgical treatment of patients with multifocal atherosclerosis with coronary and brachiocephalic vessels were obtained in 61 (98.4%) patients. Within 12 months after surgical treatment, the number of unsatisfactory results increased to 4 cases, however, this was not associated with the chosen surgical treatment method, but was due to the progression of the underlying disease (atherosclerosis) or complication of the concurrent pathology (hypertension), where acute disorders were recorded cerebral circulation. The algorithm of diagnostics is developed and the criteria of decision making are determined, the basic indications concerning the choice of approach of surgical treatment this category patients. It has been established that one step surgeries are recommended for the patients with critical lesions of coronary arteries combined with carotid artery pathology, in particular, unstable atherosclerotic plaques and low perfusion reserve of the brain and the myocardium. Conclusion. By using the proposed clinical decision making algorithm, every patient may benefit from the choice of the best method of either one-step or staged surgical treatment, whichever is more suitable. One-step surgeries are recommended for the patients with circulatory decompensation in both affected arterial territories. Staged surgical treatment may be used in patients with stable progression of coronary heart disease, without clinically significant neurological disorders.